Influence of overweight in elderly patients undergoing vaginal surgery due to pelvic floor disorders - Tuschy, Benjamin; Berlit, Sebastian; Kehl, Sven; Sütterlin, Marc; Bussen, Stefanie (In vivo, 2012)
Aim: To evaluate the feasibility and safety of vaginal surgery for treatment of genital prolapse in overweight compared to normal weight patients aged 50 years or older. Patients and Methods: We retrospectively reviewed the perioperative data of 93 patients aged between 50 and 87 years undergoing surgery due to pelvic floor disorders. A total of 54 women had a body mass index (BMI) of 25 kg/m2 or higher and were defined as the study collective. Thirty-nine patients undergoing similar surgical procedures during the same period of time had a BMI less than 25 kg/m2 and served as the control group. Operating time, duration of hospital stay, intra- and postoperative complications were evaluated as comorbidities. χ2-test, Fisher's exact test, Student's t-test and non-parametric Mann-Whitney U-test were applied to compare the results of both collectives. Results: There were no significant differences between study and control collectives regarding time of surgery, duration of hospital stay or intra- and postoperative complications, although a significant difference was found with regard to the prevalence of pre-existing diabetes mellitus (17% in the study group, versus 5% in the control group, respectively, Fisher's exact test: p=0.04). Conclusion: Overweight in elderly patients undergoing vaginal surgery due to pelvic floor disorders does not affect the perioperative outcome and is not a risk factor for perioperative complications.
Published online November 16, 2012
Keine DOI vorhanden
Gesehen am 24.09.2018